Bank management : text and cases - Hempel, George H.; Simonson, Donald G. (New York : John Wiley and Sons, 1999)
The changing nature of banking in the U.S. Understanding a Bank's financial statements. Evaluating a bank's returns, risks and overall performance. Foundations of value in banking. Asset and liability management and the Yield curve. The acquisition and cost of bank funds. Measuring and providing reserves and liquidity. Managing the security portfolio. Managing bank capital. The bank credit organization. Credit selection, underwriting and portfolio diversification. Consumer lending. Financial futures and forwards. Interest rate options. Interest rate swaps. International banking.
Keywords: Finance; Economics; Banks; Bank management; Bank management -- Case studies